EFFECT OF CAREGIVING OF CHILDREN WITH AUTISM SPECTRUM DISORDER ON THE CAREGIVERS’ SOCIAL WELLBEING IN SELECTED INTEGRATED PRIMARY SCHOOLS IN NAIROBI COUNTY, KENYA - Mary Wanja Kanja; Margaret Mwenje; Perminus Githui (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Social wellbeing is an essential part of general wellbeing of human beings because it shields individuals from social isolation by promoting positive relations. However, social challenges associated with the caregiving of children with Autism spectrum disorder (ASD) are likely to impede the caregivers’ of children with ASD from achieving their social well-being. ASD is a neurodevelopmental childhood disorder that has no physical marker. It is characterized by peculiar behaviors that are socially intolerable. The purpose of this study was to examine how caregiving of children with ASD affect the caregivers’ social wellbeing. Social Ecological System Theory (SEST) and Cognitive Behavioral Theory (CBT) guided the study. The study used a qualitative phenomenological approach and purposive sampling method to select 24 informal caregivers and four formal caregivers from selected integrated primary schools in Nairobi County, Kenya. The study used in-depth interviews and focus group discussions (FGDs) to collect data from the caregivers of children with ASD. Data was captured using tape recording and field notes. Verbatim transcription was employed. QSRN N’vivo 10 data software was used to simplify and analyze the data. The findings revealed that caregiving of children with ASD affect the caregivers’ social wellbeing in the selected integrated primary schools in Nairobi County. The study recommends creation of public awareness about ASD, training for the caregivers to equip them with skills to manage the difficult behaviors exhibited by the children with ASD, availability of affordable therapies and mental health support to the caregivers.